APPLICATION OF HEAT-INSULATING COMPOSITE GYPSUM FOR ENERGY-EFFICIENT CONSTRUCTION (Spectrum Journal of Innovation, Reforms and Development, 2022)
The article deals with the use of finishing slabs from gypsum heat-insulating composite materials based on industrial waste in energy-efficient construction, the compositions and properties of these materials are considered.